Pola Perkembangan Penggunaan Lahan Dan Struktur Ruang Di Sekitar Wilayah Eskploitasi Minyak Bumi Di Kota Duri - Sandri, Dian; Rudiarto, Iwan (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
City’s development influenced by its natural resource, petroleum is one of them. Petroleum exploration and production activities become the trigger of city’s development which is accompanied by infrastructure and facilities provision, such as transportation access toward petroleum field location. It also provokes the migration activity where people come to gain new opportunity and better life, so it creates new population concentration in those areas. Petroleum industry started with land clearing which is usually by reusing land function. Land use in particular area related with population growth and the activity, the more population figures and their activities increase, it will affect the portion of land use development. In order to response this issue, a research which aim to identify the urban structure and land use development in the petroleum exploitation area is needed, with the research location in Duri, Bengkalis, Riau Province, by considering the periods from 1995 to 2015. This research is using a quantitative method, and supported by identification, comparative, descriptive analysis. While to describe the development of existing condition in the research location, it use GIS software. Comprehensive analysis is done to acknowledge the urban structure and land use development in the exploitation area in Duri. The result of this research are land use development in periods from 1995 to 2015 are affected petroleum field location to urban structure growth in Duri, built up area growth 913.74 Ha in 1995 to 1,583.42 Ha in 2005, and 1,962.02 Ha in 2015. Firstly, built up area growth in along the main transport lines. But over time, towards the development of the spatial structure leads to the east near the Duri oil field and to the north close to oil fields Sebangar in 2005. In 2015 the development of the urban structure began to turn towards the west and south, where the area close to petroleum field location Petani, Pematang and Rangau.